Efektivitas Bahan Ajar Bangun Ruang Sisi Datar Menggunakan 5E Instructional Model terhadap Aktivitas dan Hasil Belajar - Swaditya Rizki; Syutaridho Syutaridho (UNIVERSITAS MUHAMMADIYAH METRO, 2014)
The objective of this study was to know the effectiveness of teaching materials solids with flat side which was developed using the 5E instructional model against the activities and learning outcomes in eighth grade students in Junior High School State 2 Batanghari. In this study using the methodology of development research with formative type according to Tessmer (1993), namely the development of teaching materials of solids with flat side. Research procedure using 4 stages namely self evaluation, expert review and one-to-one, small group, and field tests. The results showed that the teaching material included in the category of valid and good for use. Then the average of class activity from the observation obtained a score of 10.3, it’s means that the category scores included into the active category, and then the average of learning outcomes was 71.38 where the scores included into the good category .